African dominion : a new history of empire in early and medieval West Africa - Gomez, Michael A., 1955- (Princeton University Press, 2018)
A groundbreaking history that puts early and medieval West Africa in a global context Pick up almost any book on early and medieval world history and empire, and where do you find West Africa? On the periphery. This pioneering book, the first on this period of the region's history in a generation, tells a different story. Interweaving political and social history and drawing on a rich array of sources, including Arabic manuscripts, oral histories, and recent archaeological findings, Michael Gomez unveils a new vision of how categories of ethnicity, race, gender, and caste emerged in Africa and in global history more generally. Scholars have long held that such distinctions arose during the colonial period, but Gomez shows they developed much earlier. Focusing on the Savannah and Sahel region, Gomez traces the exchange of ideas and influences with North Africa and the Central Islamic Lands by way of merchants, scholars, and pilgrims. Islam's growth in West Africa, in tandem with intensifying commerce that included slaves, resulted in a series of political experiments unique to the region, culminating in the rise of empire. A major preoccupation was the question of who could be legally enslaved, which together with other factors led to the construction of new ideas about ethnicity, race, gender, and caste--long before colonialism and the transatlantic slave trade. Telling a radically new story about early Africa in global history, African Dominion is set to be the standard work on the subject for many years to come.